Endurance exercise performance: the physiology of champions - Joyner, M. J.; Coyle, E. F. (The Journal of Physiology, 2008)
Efforts to understand human physiology through the study of champion athletes and record performances have been ongoing for about a century. For endurance sports three main factors - maximal oxygen consumption Graphic, the so-called `lactate threshold' and efficiency (i.e. the oxygen cost to generate a give running speed or cycling power output) - appear to play key roles in endurance performance. Graphic and lactate threshold interact to determine the `performance Graphic` which is the oxygen consumption that can be sustained for a given period of time. Efficiency interacts with the performance Graphic to establish the speed or power that can be generated at this oxygen consumption. This review focuses on what is currently known about how these factors interact, their utility as predictors of elite performance, and areas where there is relatively less information to guide current thinking. In this context, definitive ideas about the physiological determinants of running and cycling efficiency is relatively lacking in comparison with Graphic and the lactate threshold, and there is surprisingly limited and clear information about the genetic factors that might pre-dispose for elite performance. It should also be cautioned that complex motivational and sociological factors also play important roles in who does or does not become a champion and these factors go far beyond simple physiological explanations. Therefore, the performance of elite athletes is likely to defy the types of easy explanations sought by scientific reductionism and remain an important puzzle for those interested in physiological integration well into the future.